The Correlation Between Staffing Planning by Heads of Departments and Workload with Nurse Satisfaction at Islamic Hospital Jakarta Cempaka Putih - Yuliawati Yuliawati; Harif Fadhillah; Eni Widiastuti; Muhammad Hadi (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2024)
Background: The lack of nurses compared to the planned needs has an impact on increasing workload. Workload and job satisfaction are two concepts that are closely related in the world of work. Workload refers to the number of tasks and responsibilities that must be carried out by a person in their job. Meanwhile, job satisfaction refers to the level of satisfaction a person has with their job. Methods: The purpose of this study was to determine the relationship between staff planning by the head of the room and workload with nurse job satisfaction. Methods: This study used quantitative research with descriptive research design and crosssectional approach. The sample size was 98 nurses of RSIJ Cempaka putih using stratified random sampling technique of finite population. Data collection using questionnaires and statistical tests with the Chi Square test. Results: chi square test there is a significant relationship or there is a relationship between power planning by the head of the room with nurse job satisfaction (p value = 0.031). There is a relationship between workload and nurse satisfaction (p value= 0.000). The dominant variable associated with nurse ob satisfaction is workload Conclusion: Nurses with high workloads are at risk of becoming dissatisfied with their work. Nursing management should pay attention to nurses' workloads by planning a balanced nursing workforce based on the number of staff, types of staff, and educational qualifications of nursing staff in accordance with the workload in each treatment room. Thus, the nursing care and services provided will be more professional, and nurses will feel satisfied in their work.